Non-Mitogenic Fibroblast Growth Factor 1 Enhanced Angiogenesis Following Ischemic Stroke by Regulating the Sphingosine-1-Phosphate 1 Pathway - Zou, Yuchi; Hu, Jian; Huang, Wenting; Ye, Shasha; Han, Fanyi; Du, Jingting; Shao, Mingjie; Guo, Ruili; Lin, Jingjing; Zhao, Yeli; Xiong, Ye; Wang, Xue (Frontiers in Pharmacology, 2020)
Ischemic strokes account for about 80% of all strokes and are associated with a high risk of mortality. Angiogenesis of brain microvascular endothelial cells may contribute to functional restoration following ischemia. Fibroblast growth factor 1 (FGF1), a member of FGF superfamily, involved in embryonic development, angiogenesis, wound healing, and neuron survival. However, the mitogenic activity of FGF1 is known to contribute to several human pathologies, thereby questioning the safety of its clinical applications. Here, we explored the effects and mechanism of action of non-mitogenic FGF1 (nmFGF1) on angiogenesis in mice after ischemia stroke and an oxygen-glucose deprivation (OGD)-induced human brain microvascular endothelial cells (HBMECs) injury model. We found that intranasal administration nmFGF1 significantly promoted angiogenesis in mice after stroke, and significantly increased the formation of matrigel tube and promoted scratch migration in a dose-dependent manner in OGD-induced HBMECs in vitro. However, the co-administration of an FGF receptor 1 (FGFR1)-specific inhibitor PD173074 significantly reversed the effects of nmFGF1 in vitro, suggesting that nmFGF1 functions via FGFR1 activation. Moreover, nmFGF1 activated sphingosine-1-phosphate receptor 1 (S1PR1, S1P1) in mice after stroke in vivo. S1P1 protein antagonist VPC23019 and agonist FTY720 were used to confirm that nmFGF1 promotes angiogenesis in vitro partially through the S1P1 pathway. OGD induced downregulation of S1P1 expression. The S1P1 antagonist VPC23019 blocked the stimulatory effects of nmFGF1, whereas the S1P1 agonist FTY720 exerted effects comparable with those of nmFGF1. Furthermore, PD173074 reversed the effect of nmFGF1 on upregulating S1P1 signaling. In conclusion, nmFGF1 enhanced angiogenesis in mice following stroke and OGD-induced HBMECs through S1P1 pathway regulation mediated via FGFR1 activation. This new discovery suggests the potential therapeutic role of nmFGF1 for the treatment of ischemic strokes.